1992
DOI: 10.1016/0735-1097(92)90450-2
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone therapy does not compromise subsequent heart transplantation

Abstract: Amiodarone therapy before heart transplantation may contribute to occasional pulmonary complications but does not significantly increase perioperative morbidity or mortality with the regimens used in this retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 19 publications
3
13
0
1
Order By: Relevance
“…Its main bradycardic effects are mediated through its beta receptor blocking activity. Given that the effects of amiodarone will last several weeks after transplantation (23), our finding that pretransplant amiodarone is associated with bradycardia is plausible, and agrees with several studies which demonstrated that pretransplant amiodarone leads to lower post-transplant heart rates (23)(24)(25)(26). The study by Montero et al (2) looked at the effect of pretransplant amiodarone on pacing requirements after transplantation.…”
Section: Discussionsupporting
confidence: 86%
“…Its main bradycardic effects are mediated through its beta receptor blocking activity. Given that the effects of amiodarone will last several weeks after transplantation (23), our finding that pretransplant amiodarone is associated with bradycardia is plausible, and agrees with several studies which demonstrated that pretransplant amiodarone leads to lower post-transplant heart rates (23)(24)(25)(26). The study by Montero et al (2) looked at the effect of pretransplant amiodarone on pacing requirements after transplantation.…”
Section: Discussionsupporting
confidence: 86%
“…In 2 retrospective series of adult HTx recipients, pretransplant amiodarone use was associated with lower heart rates and higher incidence of atrial pacing without an effect on mortality, rejection, or inotropic support. 15,16 This is largely attributed to the long half-life of amiodarone, which can linger for months after its discontinuation. In addition to amiodarone, other antiarrhythmics could have contributed to the increase in PPM implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Romhilt et a14 studied 13 long-term survivors of cardiac transplantation. Three (23%) patients experienced non-sustained paroxysmal supraventricular tachycardia within the first 30 days, five (38%) experienced sinus bradycardia (undefined), and three (23%) subsequently required implantation of a permanent pacing system.…”
Section: Discussionmentioning
confidence: 99%